"Special K" Drug on Adolescent Rats: Oxidative Damage and Neurobehavioral Impairments. (14th March 2019) - de Carvalho Cartágenes, Sabrina; Fernandes, Luanna Melo Pereira; Carvalheiro, Taiana Cristina Vilhena Sarmento; de Sousa, Thais Miranda; Gomes, Antônio Rafael Quadros; Monteiro, Marta Chagas; de Oliveira Paraense, Ricardo Sousa; Crespo-López, Maria Elena; Lima, Rafael Rodrigues; Fontes-Júnior, Enéas Andrade; Prediger, Rui Daniel; Maia, Cristiane Socorro Ferraz
Abstract : Ketamine is used in clinical practice as an anesthetic that pharmacologically modulates neurotransmission in postsynaptic receptors, such as NMDA receptors. However, widespread recreational use of ketamine in "party drug" worldwide since the 1990s quickly spread to the Asian orient region. Thus, this study aimed at investigating the behavioral and oxidative effects after immediate withdrawal of intermittent administration of ketamine in adolescent female rats. For this, twenty female Wistar rats were randomly divided into two groups: control and ketamine group (n = 10 /group). Animals received ketamine (10 mg/kg/day) or saline intraperitoneally for three consecutive days. Three hours after the last administration, animals were submitted to open field, elevated plus-maze, forced swim tests, and inhibitory avoidance paradigm. Twenty-four hours after behavioral tests, the blood and hippocampus were collected for the biochemical analyses. Superoxide dismutase, catalase, nitrite, and lipid peroxidation (LPO) were measured in the blood samples. Nitrite and LPO were measured in the hippocampus. The present findings demonstrate that the early hours of ketamine withdrawal induced oxidative biochemistry unbalance in the blood samples, with elevated levels of nitrite and LPO. In addition, we showed for the first time that ketamine withdrawal induced depressive- and anxiety-like profile, as well as short-term memory impairment in adolescent rodents. The neurobehavioral deficits were accompanied by the hippocampal nitrite and LPO-elevated levels.